The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.12816/0014417
|View full text |Cite
|
Sign up to set email alerts
|

Misunderstanding of the Term DNR in a Middle - Eastern Teaching Hospital

Abstract: Background: Do-not-resuscitate (DNR) order has been practiced for many years; though it is one of the most commonly misunderstood and misinterpreted orders in medical practice. It has many ethical, legal, geographic, religious and cultural aspects that contribute to this misunderstanding. Objective: To assess the perception amongst the acute specialties who deal with DNR orders. Design: A Cross-Sectional Questionnaire Type Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Our findings evidence that the concept of EOLC, in ICUs in Bahrain, is poorly understood and articulated. 36 A finding cannot be attributed only to cultural values. Studies in Western contexts have also highlighted the ambiguity and uncertainty practitioners experience in attempting to accurately predict when the death of a patient will occur.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings evidence that the concept of EOLC, in ICUs in Bahrain, is poorly understood and articulated. 36 A finding cannot be attributed only to cultural values. Studies in Western contexts have also highlighted the ambiguity and uncertainty practitioners experience in attempting to accurately predict when the death of a patient will occur.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, some physicians were not adequately informed of the DNR order to conduct these discussions with patients and family. 22…”
Section: Discussionmentioning
confidence: 99%
“…Culturally, there is a pervasive misinterpretation of the term across various regions in the Middle East. A study done by Ismail et al (2015) found that both patients and family members equate the DNR order with watching the patient die without providing any curative or palliative relief. Moreover, some physicians were not adequately informed of the DNR order to conduct these discussions with patients and family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Although, the concept of DNR order does not mean not to treat the terminally ill patient, this concept is often misunderstood and poorly complied by health professionals. 9 So, to effectively use and prevent misuse of DNR order, health professional must be educated about DNR. 4 Nursing care is directed towards meeting the comprehensive needs of patients and their families to prevent and relieve the symptoms and suffering of patients that are commonly associated with illness and dying.…”
Section: Introductionmentioning
confidence: 99%